Perception of teachers from the state network of the Municipality of São João da Barra - RJ about the use of Google Classroom in emergency remote education (Research, Society and Development, 2020)
Emergency Remote Teaching (ERT) has the main objective of providing temporary access to the teaching and learning process with the support of Digital Technologies (DT) reliably, during an emergency or crisis.  In this sense, a survey was carried out with teachers from the state public network in the municipality of São João da Barra, in the interior of Rio de Janeiro, to investigate the perception of teachers about the use of the Google Classroom platform during the ERT period.  The research was developed according to a qualitative approach and was exploratory.  This article aims to present an analysis of the data collected through an online questionnaire.  The results signaled that a Google Classroom platform was well accepted in the view of the teachers participating in the research.  Some positive and negative points were observed by the teachers.  The positive aspects were corrected to the possibility of the student maintaining the link with the school, an interaction between teacher and student through DT and an excellent junction between education and technology, a bridge that seeks to facilitate the understanding and consequent student learning.  The negative points were the students who do not have access to the teaching platform in a social exclusion because they do not have computers, the lack of internet by many students, the lack of maturity and commitment in this type of education and of not yet feeling comfortable recording video.